ESTIMATION OF VARIABILITY PARAMETERS FOR YIELD AND ITS COMPONENT TRAITS IN GROUNDNUT (ARACHIS HYPOGAEA L.) - A. S. PATIL,; A. A. PUNEWAR,; H. R. NANDANWAR,; K. P. SHAH, (The Bioscan, 2014)
In the present investigation 58 Spanish bunch groundnut genotypes were used for variability studies in 16 plant characters. Analysis of variance revealed significant differences among the genotypes for all the characters studied. Maximum broad sense heritability was recorded for days to 50% flowering (97.1% (S1), 97.3% (S2), 98.0% (S3) followed by plant height (96.7% (S1), 97.1% (S2), 97.1% (S3) and 100-kernels weight (96.0% (S1), 96.0% (S2), 96.4% (S3). The maximum genetic advance was found for seed dormancy (36.9% (S1), 39.2% (S2), 40.8% (S3) followed by 100-kernels weight (29.3% (S1), 32.1% (S2), 32.2% (S3) and plant height (33.3% (S1), 32.9% (S2), 27.5% (S3). In general, moderate to high heritability coupled with moderate to high genetic advance for days to 50% flowering, plant height, 100-pods weight, 100-kernels weight, shelling percent and harvest index, indicated the involvement of additive gene action and scope of improvement in these traits through selection.